Credit Risk Management in Financial Institution: Comparative Study in Islamic and Conventional Banking - Galuh Tri Pambekti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2019)
Credit and financing problems at conventional banks and Islamic banks are related to how businesses that have been financed by banks can be run, whether the loan recipient has actually run the business as stated in the contract or the business manager has been denied. The purpose of this study was to determine the differences in Non-Performing Loans in conventional banks and Non-Performing Financing of Islamic banks. Hypothesis testing techniques in this study used the first two choices of independent sample t-test if the data were normally distributed so the classical assumptions were tested first to ensure that the data used by researchers had a normal distribution and if the data were not normally distributed will use the Mann Whitney test to test the difference between Non Performing Loans and Non Performing Financing in Islamic commercial banks and conventional banks.. So the results of this study indicate that there are differences between PT. Bank Mandiri and NPF of PT Bank Syariah Mandiri, or it can be said there is a difference between ratios that indicate the ability of bank management in managing loans or financing problems provided by PT. Bank Mandiri and PT Bank Syariah Mandiri.